2008
DOI: 10.1016/j.cell.2008.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Homeodomain Specificities Allows the Family-wide Prediction of Preferred Recognition Sites

Abstract: We describe the comprehensive characterization of homeodomain DNA-binding specificities from a metazoan genome. The analysis of all 84 independent homeodomains from D. melanogaster reveals the breadth of DNA sequences that can be specified by this recognition motif. The majority of these factors can be organized into 11 different specificity groups, where the preferred recognition sequence between these groups can differ at up to four of the six core recognition positions. Analysis of the recognition motifs wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
528
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 420 publications
(571 citation statements)
references
References 55 publications
23
528
0
1
Order By: Relevance
“…Promoter analysis of Cxs that are expressed in the VCS (Cx40, Cx43, Cx45, and Cx30.2) revealed that the Gja1 promoter contains an evolutionarily conserved element harboring a putative Irx3 binding site (37)(38)(39), which overlaps with an Nkx2-5 binding motif (Irx/NKE) immediately upstream of conserved T-box binding elements (Fig. 4E).…”
Section: Resultsmentioning
confidence: 99%
“…Promoter analysis of Cxs that are expressed in the VCS (Cx40, Cx43, Cx45, and Cx30.2) revealed that the Gja1 promoter contains an evolutionarily conserved element harboring a putative Irx3 binding site (37)(38)(39), which overlaps with an Nkx2-5 binding motif (Irx/NKE) immediately upstream of conserved T-box binding elements (Fig. 4E).…”
Section: Resultsmentioning
confidence: 99%
“…Other work had shown the importance of these amino acids for DNA recognition in other homeoproteins. 19,20 We observed that the Caup HD * mutant proteins were located in both the nucleus and in the cytoplasm of wing discs cells. This identified amino acids N51, R55 and R57 of the Caup homeodomain as part of a Nuclear Localization Signal (NLS, Fig.…”
Section: The Iro-box As An Important Domain For the Regulation Of Celmentioning
confidence: 86%
“…These TFs act by controlling the expression of unique sets of downstream target genes during embryogenesis [2]. Most TFs recognize short DNA-binding sites that are often also similar among members of the same family [3]. Just how proteins with overlapping DNA-binding specificities carry out distinct functions in vivo is a fundamental and unresolved question in biology.…”
Section: Introductionmentioning
confidence: 99%
“…These TFs are organized in paralog groups whose numbers differ between species, but whose functions have been evolutionarily conserved for assigning distinct cell fates along the anteriorposterior (AP) axis of all bilaterian embryos [4]. Despite their specific functions in vivo, classic and high throughput assays have established that Hox proteins preferentially recognize similar AT-rich nucleotide sequences as monomers in vitro [3]. These converging observations strongly suggest that each Hox protein may require the presence of additional DNA-binding partners to recognize their correct set of target genes in vivo.…”
Section: Introductionmentioning
confidence: 99%